Atomic transport in B2-ordered Al(Fe, Ni) alloys: Tracer-interdiffusion couple approach. (November 2020) - Muralikrishna, G. Mohan; Esin, Vladimir A.; Kulkarni, Kaustubh N.; Murty, B.S.; Wilde, Gerhard; Divinski, Sergiy V.
Abstract: A novel tracer-interdiffusion couple technique is utilized to measure the concentration-dependent tracer- ( 59 Fe) diffusion coefficients in the B2-ordered Al50 (Ni, Fe)50 alloys at 1373 K in a single experiment. The influence of variable molar volume on the diffusion coefficients is examined. The tracer diffusion coefficients determined under chemical gradients are shown to be in an excellent agreement with the diffusivities measured independently for homogeneous alloys. The tracer diffusion coefficients of Fe are observed to increase strongly with an increase of the Fe concentration. Strong up-hill diffusion of Al hinders a reliable determination of the interdiffusion coefficients with a single diffusion couple. The results confirm a high potential of the tracer-interdiffusion couple technique for producing highly accurate concentration-dependent mobility data in multi-component systems. Graphical abstract: Image 1 Highlights: A novel tracer-interdiffusion couple method verified thoroughly for the first time. Tracer diffusion coefficients estimated in Al50 (Fe, Ni)50 by single diffusion couple. Examination of influence of variable molar volume on diffusion coefficients. Excellent agreement with the conventional independent measurements. Impeccable results confirm outstanding efficacy of tracer-interdiffusion method.